Vapour-phase deposition of oriented copper dicarboxylate metal–organic framework thin films. Issue 68 (1st August 2019) - Stassin, Timothée; Rodríguez-Hermida, Sabina; Schrode, Benedikt; Cruz, Alexander John; Carraro, Francesco; Kravchenko, Dmitry; Creemers, Vincent; Stassen, Ivo; Hauffman, Tom; De Vos, Dirk; Falcaro, Paolo; Resel, Roland; et al.
Abstract : Vapour-phase deposition of copper dicarboxylate metal–organic framework thin films with an out-of-plane orientation and accessible porosity. Abstract : Copper dicarboxylate metal–organic framework films are deposited via chemical vapour deposition. Uniform films of CuBDC and CuCDC with an out-of-plane orientation and accessible porosity are obtained from the reaction of Cu and CuO with vaporised dicarboxylic acid linkers.